Antifungal activity of five different essential oils in vapour phase for the control of Colletotrichum gloeosporioides and Lasiodiplodia theobromae in vitro and on mango. (12th December 2015) - Perumal, Anand Babu; Sellamuthu, Periyar Selvam; Nambiar, Reshma B.; Sadiku, Emmanuel Rotimi
Summary: Mango fruit has high commercial value; however, major postharvest losses are encountered throughout the supply chain due to postharvest diseases. These results lead to the search for natural fungicide for postharvest diseases control. The antifungal effects of five essential oils (thyme, clove, cinnamon, anise and vitex) were assessed by disc volatilisation method. Thyme oil vapours at 5 μL per Petriplate, and clove and cinnamon oil at 8 μL per Petriplate showed 100% growth inhibition of mango pathogens in vitro . GC/MS analysis of essential oil showed thymol (23.88), o‐cymol (23.88) and terpinolene (23.88) as the major constituents of thyme oil. Clove and cinnamon oils contain 3‐allyl‐2‐methoxyphenol (37.42%) and benzofuran 3‐methyl (17.97%), respectively. Thyme oil as a fumigant at 66.7 μL L −1 showed a significant ( P < 0.05) inhibition on postharvest pathogens of mango fruits stored at 25 °C for 6 days. Results of our study suggest the possibility of using thyme oil as an alternate natural fungicide to manage postharvest diseases in mango. Abstract : Antifungal effect of five essential oils (thyme, clove, cinnamon, anise and vitex) was determined by disc volatilization method. Thyme oil at 5 μL/Petriplate and 66.7 μL/L on artificial infected mangoes provided significant control on the postharvest diseases. The findings recommend that thyme oil vapors could be used as alternate natural fungicide to control the common postharvest diseases in mango.